Mainstreaming gender dimensions into water resources management within the MWRI and role of SRU/NWRC within GEWAMED project - Aboul-Fotoh N.Z. (Institutional coordination and streamlining partners activities in the framework of GEWAMED project, 2006)
The integrated management of the different water resources is considered of a vital importance for achieving an overall development in the water sector within the South East Mediterranean Region (SEMR). However, human resources development has to proceed in parallel with the engineering conceptual efforts of the Integrated Water Resources Management (IWRM). The role of each individual within the society can be considered the promoting factor for achieving real development. This global perspective should include both rural and urban areas. Gender equity, equality, and women participation issues are recognized as key elements for improving the human resources development within the water resources management. The current paper illustrates the ongoing gender activities within the Ministry of Water Resources and Irrigation (MWRI) in Egypt, in an effort to address the past experiences and the reached achievements. Moreover, a full description of the launching process for mainstreaming gender dimensions into water resources development and management in cooperation with SEMR countries and the proposed new communication and networking actions for that purpose are presented. The Strategic Research Unit (SRU) within the National Water Research Center (NWRC) in full cooperation with the different MWRI Gender Focal Points is the implementing agency for the newly presented initiative.
First Regional Coordination Project of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2006/02/20-22, Bari (Italy)